Approximation with Chlodowsky variant of Kantorovich-Stancu-operators employing associated λ-polynomials - Nusrat Raza; Manoj Kumar (Journal of Inequalities and Applications)
Abstract This article explores a Chlodowsky-type extension of the Kantorovich variant of Szász operators based on the associated λ-polynomials. The convergence properties of these operators are established by employing the universal Korovkin-type property, and the order of approximation is determined using the classical modulus of continuity and the Ditzian-Totik modulus of continuity. Additionally, the αβ-statistical convergence properties of the operators are derived. Additional approximation outcomes are also formulated within the context of the polynomial weighted space. Finally, the theoretical results are supported by numerical and graphical examples for different parameters.